Improving Food Security with Aquaculture: A Collaborative Effort to Empower Tilapia Farmers in Kemiri Village, Mojokerto - Hendarto, Totok; Budiyanto, Didik; Sutarmin, Sutarmin; Ardianik, Ardianik (CV. BImbingan Belajar Assyfa, 2025)
Kemiri Village, located in Pacet District, Mojokerto Regency, has significant fisheries potential but faces various obstacles such as limited technology adoption, management skills, and suboptimal market access. Through a community service initiative involving teachers, lecturers, students, practitioners, researchers, and the active participation of the community and local partners, this program is designed to strengthen the capacity of tilapia farmers to support village food security. The approach used includes problem identification through focus group discussions, training on environmentally friendly aquaculture technology innovations, and mentoring in the implementation of a fishery business management system. This activity also integrates digital marketing education and training in independent feed production using local ingredients. Periodic evaluations are conducted to measure skill improvements, production efficiency, and the economic impact on farmers. The program results show improved fish farming skills, reduced production costs, and significant increases in yields. Furthermore, it has formed a more empowered farmer group with access to a wider market. The multi-stakeholder synergy within this program has proven effective in addressing various local challenges and promoting sustainable development, with the ultimate goal of improving the well-being of the Kemiri Village community.